Crystal and Magnetic Structure of Sr2BIrO6 (B = Sc, Ti, Fe, Co, In) in the Framework of Multivalent Iridium Double Perovskites. Issue 30 (30th September 2015) - Kayser, Paula; Alonso, Jose A.; Mompeán, Federico J.; Retuerto, Maria; Croft, Mark; Ignatov, Alexander; Fernández‐Díaz, Maria T.
Abstract: The preparation, crystal structure and magnetic properties of Sr2 BIrO6 (B = In, Sc, Fe, Co or Ti) oxides are reported. For B = Sc, Fe, Co or In materials, X‐ray and neutron powder diffraction (NPD) studies confirm the presence of 1:1 B‐ordered perovskite‐like structures crystallizing in the monoclinic I 2/ m and P 21 / n space groups, with unit‐cell parameters a ≈ √2 a 0, b ≈ √2 a 0, c ≈ 2 a 0 and β ≈ 90°. Sr2 TiIrO6 is described as a disordered perovskite with orthorhombic symmetry in the Pbnm space group. For B = Fe and Co, low‐temperature NPD data and magnetic measurements indicate the existence of an antiferromagnetic structure resulting from the Fe 3+ /Co 3+ magnetic moment interaction. X‐ray absorption spectroscopy corroborates that the oxidation states of B and Ir are 3+ and 5+, respectively. The bond lengths and other structural features are discussed in the framework of other recently reported iridium double perovskites where iridium adopts tetravalent, pentavalent and hexavalent oxidation states, and in the wider context of Sr double perovskites. Abstract : Selected members of the Sr2 BIrO6 family, containing cations of different nature and Ir with oxidation states 4+, 5+ and 6+, have been obtained under synthesis conditions carefully chosen to select the required iridium valence. Additionally, the influence of the M n + radius on the internal parameters, obtained from an X‐ray neutron powder diffraction (NPD) analysis, is discussed.